The dynamic group environment in sport and exercise. (May 2019) - Eys, Mark; Bruner, Mark W.; Martin, Luc J.
Abstract: Although researchers have offered insights across a range of topics (e.g., cohesion, leadership, roles, etc.), a recent review suggested that the field of group dynamics in physical activity has a strong potential for growth as an area of focus for research (Eys & Spink, 2016). The objectives of the present review are to (a) highlight the importance of group dynamics within physical activity contexts, (b) review progress made on select but key longstanding and emerging topics, and (c) provide suggestions for future research that will facilitate the progression of the field. To this end, a case is made for the necessity to understand group dynamics based on the prevalence of groups in sport and exercise contexts, in addition to the potential for satiating the fundamental need to belong (Baumeister & Leary, 1995). Finally, key topics and future research directions are embedded within four broad sections including (a) setting the stage (e.g., the group environment, team selection, and socialization), (b) structural issues (e.g., roles, leadership), (c) group processes and emergent states (e.g., cohesion), and (d) the application of group dynamics principles. Overall, there are tremendous opportunities for researchers to contribute to the theory, research, and practice of group dynamics in sport and exercise. Highlights: Group contexts are pervasive and influential in physical activity. Understanding group dynamics in sport and exercise contexts is critical. Evidence provided across group development, structure, processes, and emergent states. Need to further expand knowledge for the application of group dynamics principles. Significant opportunities for future research across many topics within this field.